The Effect of Computational Thinking and Prior Mathematical Ability on Problem Solving Skills - Mar Athul Wazithah T.; Fadhilah Nur Sa'diyyah - (Research Collaboration Community (Rescollacom), 2026)
This study investigates the influence of computational thinking and prior mathematical ability on students’ mathematical problem-solving skills. The research was conducted using a quantitative correlational approach involving second-semester students of the Mathematics Education Study Program at Universitas Negeri Makassar in the 2024/2025 academic year, specifically in the Basic Geometry course. Data were collected through written tests designed to measure computational thinking, prior mathematical ability, and problem-solving skills. The collected data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that both computational thinking and prior mathematical ability have a significant positive effect on students’ mathematical problem-solving skills, both partially and simultaneously. Computational thinking shows a more dominant contribution compared to prior mathematical ability, indicating that students who are capable of decomposing problems, recognizing patterns, abstracting concepts, and constructing systematic solutions tend to perform better in solving mathematical problems. Meanwhile, prior mathematical ability plays a crucial role as a cognitive foundation that supports students in understanding and applying relevant concepts during the problem-solving process. Furthermore, the regression model demonstrates that both variables contribute substantially to explaining variations in problem-solving ability, suggesting that these factors are essential components in developing higher-order thinking skills. The findings imply that mathematics instruction, particularly in Basic Geometry, should integrate computational thinking approaches while strengthening students’ foundational knowledge. Such integration is expected to enhance students’ ability to solve complex mathematical problems effectively.